PMO competency framework - Roden, Eileen; Hindley, Carol; Scott, Lindsay 1974- (House of PMO, 2021)
The PMO Competency Framework is a guide for PMO professionals interested in assessing and developing organisation-wide, team and personal competences within a PMO environment. This PDF provides a standard and a toolset to allow PMO professionals to understand, assess and develop the skills, behaviours and experience to achieve their PMO goals and career potential. Aligned with the House of PMO Essentials examinations from APMG International; it serves as an official reference guide for the course.
Includes bibliographical references
Keywords: Project management -- Handbooks, manuals, etc; Gestion de projet; Guides, manuels, etc; Project management; Handbooks and manuals